2023
DOI: 10.1111/all.15640
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus causes aberrant epidermal lipid composition and skin barrier dysfunction

Abstract: Background: Staphylococcus (S) aureus colonization is known to cause skin barrier disruption in atopic dermatitis (AD) patients. However, it has not been studied how S. aureus induces aberrant epidermal lipid composition and skin barrier dysfunction.Methods: Skin tape strips (STS) and swabs were obtained from 24 children with AD (6.0 ± 4.4 years) and 16 healthy children (7.0 ± 4.5 years). Lipidomic analysis of STS samples was performed by mass spectrometry. Skin levels of methicillin-sensitive and methicillin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…S. aureus indirectly influences the CER composition via cytokine mediation (IL-1β, TNF-α and IL-33) that inhibits expression of fatty acid elongases in keratinocytes. 44 Furthermore, IL-33 showed a positive correlation between S. aureus and several short-chain CERs. Conversely, Streptococcus was inversely correlated with IL-31 and IL-33, as these findings were mainly driven by Inuit children, and S. aureus is known to promote the expression of these cytokines, the association could be explained from the lower abundance of S. aureus in Inuit skin.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…S. aureus indirectly influences the CER composition via cytokine mediation (IL-1β, TNF-α and IL-33) that inhibits expression of fatty acid elongases in keratinocytes. 44 Furthermore, IL-33 showed a positive correlation between S. aureus and several short-chain CERs. Conversely, Streptococcus was inversely correlated with IL-31 and IL-33, as these findings were mainly driven by Inuit children, and S. aureus is known to promote the expression of these cytokines, the association could be explained from the lower abundance of S. aureus in Inuit skin.…”
Section: Discussionmentioning
confidence: 96%
“…This might in part be related to the increased S. aureus colonization in Danish AD skin. S. aureus indirectly influences the CER composition via cytokine mediation (IL‐1β, TNF‐α and IL‐33) that inhibits expression of fatty acid elongases in keratinocytes 44 . Furthermore, IL‐33 showed a positive correlation between S. aureus and several short‐chain CERs.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, microbiota prevents the colonization of the pathogenic microorganisms, regulates, and improves epithelial barrier functions [ 28 ]. In barrier defective tissues, type 2 immune responses are initiated against commensal microbes as well as facultative pathogens [ 29 ]. Staphylococcus aureus ( S. aureus ) is the most abundant bacterium colonizing damaged tissues of the respiratory system and the skin.…”
Section: Risk Factors Of Epithelial Barrier Dysfunctionmentioning
confidence: 99%
“…Staphylococcus aureus colonization is associated with atopic dermatitis and contributes to skin inflammation [41]. Analysis of children with atopic dermatitis and normal controls demonstrated that atopic dermatitis skin colonized with Methicillin-resistant S. aureus (MRSA) had aberrant skin lipid profiles and barrier dysfunction [42 ▪▪ ]. Another study also demonstrated altered lipid profiles, as well as distinct microbiome profiling with increased Firmicutes and decreased Actinobacteria, Proteobacteria, and Bacteroidetes at the phylum level in lesional atopic dermatitis skin [43].…”
Section: Staphylococcus Aureus and The Microbiomementioning
confidence: 99%